The Influence of Sharia Financial Literacy, Religiosity, Financial Self-Efficacy, and Financial Locus of Control as Mediating Effects on the Financial Behavior of Qris Users of Islamic Banks. - Hidayatul Fitriani; Zefri Maulana; Tajul Ula; Juli Dwina Puspita Sari (Faculty of Islamic Business and Management, 2025)
This study aims to analyze the determinants of public interest in the use of QRIS in Sharia Banks with a focus on Langsa City - one of the cities in Aceh which is a province that implements the Islamic financial system. The independent variables tested included promotion, religiosity, education, and financial ability. Shariah financial literacy is considered as an intermediary variable that plays a role in connecting independent variables with dependent variables, namely interest in using QRIS. Considering that literacy and interest in using digital finance in Aceh, especially Langsa City, are still low, this research is important in understanding the factors that affect public interest.This study involved 100 respondents from Langsa City who were randomly taken with a quantity determined through the method of determining the number of Slovin. The analysis method used in this study is the Structural Equation Modeling - Partial Least Squares (SEM-PLS) Method which serves to identify whether the effect of independent variables on dependent variables occurs directly, or through intermediate variables (intermediation). The results of the study show that promotion, religiosity, education, and financial ability significantly affect financial literacy, which then has a positive impact on interest in using QRIS.These findings are expected to help Islamic banking and the government in designing strategies to increase the adoption of digital financial services in Aceh, especially Langsa City.